PENGUJIAN KUALITAS KAYU LAPIS UNTUK KONTRUKSI BANGUNAN YANG BEREDAR DI PASARAN KOTA BENGKALIS - Somadona, Sonia; Sribudiani, Evi; Arlita, Tuti (Wahana Forestra: Jurnal Kehutanan, 2016)
Plywood is a composite product in form of an artificial board made of veneer sheets that were bonded together with an arrangement of perpendicular intersection. The quality of plywood circulating in Bengkalis City market was examined onits quality of the surface, inside and back space, moisture content and the thickness of its swell . The examination on the quality of plywood for construction of buildings circulating in Bengkalis City Market was using the standard of SNI 01-5008.2-1999. The test results of 4 plywood trademarks circulating in the market of Bengkalis City on its surface quality was showing that the product as known as Arwana and Tunas trademarks were belong to C class, Fortune that has quality B class, and OFR was on A class quality. While the quality inside of plywood of brand mark as Arwana, Tunas and Fortune were including to class A quality (overlap defect), but those 2 natural and technical defects is not including to SNI requirement criterias (slit and length), OFR trademark plywood’s inside quality was included into A classon its natural and technical defect criteria. Further, the quality of plywood’s back space of those 4 trademarks circulating in Bengkalis City were included into the standard SNI 01-5008.2-1999. The examintaion of moisture content in accordance to SNI 01-5008.2-1999 standard showed that Fortune and OFR trademark were fulfilling the requirement standard of 14%, while Arwana and Tunas were having higher water content (≥ 20%). At last, the thickness swell of all trademarks were in conformity with the SNI 01-5008.2-1999, in which reqiuring its thickness of 12%.